Development and validation of a new RP-HPLC method for the determination of process related impurities in pioglitazone hydrochloride - Prava, Venkata Raj Kumar; Seru, Ganapaty (European Journal of Chemistry, 2014)
A reversed phase high performance liquid chromatographic method for the determination of process related impurities in pioglitazone hydrochloride was developed and validated. High-quality separation was achieved on a Luna C18 column (150 mm × 4.6 mm, 3 µm) using gradient elution at a flow rate of 1 mL/min and a column temperature of 45 °C. UV detection was performed at 254 nm. The validation was performed according to the International Conference on Harmonization (ICH) guidelines. In addition, the solution stability and method robustness were examined. The method gives satisfactory separation of impurities of pioglitazone hydrochloride and so it is suitable for quantification of the process related impurities as well as for the assay of the active compound.